(untitled) (Eureka Journal of Business, Economics & Innovation Studies, 2026)
Research Objectives: The current research aimed to identify the impact of inclusive leadership behaviors on work passion, through an analytical study of the opinions of a sample of teaching staff at Tikrit University. Research Methodology: The research adopted the (descriptive analytical method), which is characterized by the great flexibility it provides, as it enables the diagnosis and study of reality in a more accurate manner. Data Collection Tools: The questionnaire was used as the main tool for collecting data and information related to the researched sample. Research Population and Sample: The research population consisted of teaching staff from all colleges at Tikrit University, numbering (3119) members. A purposive sample of (342) teaching staff was taken. Statistical Tools Used: The statistical programs (SPSS V.23) and (AMOS V.20) were adopted to conduct statistical analysis, using methods such as arithmetic mean, standard deviation, Pearson correlation coefficient, and T-test, F-test. Most Important Results: The results of the analytical study show that inclusive leadership behaviors have a positive and direct effect on work passion among teaching staff.